Late Occupation of the High‐Elevation Northern Tibetan Plateau Based on Cosmogenic, Luminescence, and Radiocarbon Ages. Issue 5 (16th July 2013) - Brantingham, P. Jeffrey; Xing, Gao; Madsen, David B.; Rhode, David; Perreault, Charles; van der, Jerome; Olsen, John W.
<x xml:space="preserve">Abstract</x> 10Be‐26Al cosmogenic surface exposure, optically stimulated luminescence, and radiocarbon dates from the site of Xidatan 2 (∼4300 m above sea level [asl] in the Kunlun Pass, northern Tibetan Plateau) suggest the site was intermittently and briefly occupied approximately 9200–6400 yr B.P. This age is substantially younger than expected given the late Upper Paleolithic character of the lithic assemblage, which is dominated by microlithic and unique discoidal prepared core technologies. Comparisons between Xidatan 2 and known surface lithic assemblages in the Kekexili and Chang Tang regions of the central high Plateau show not only that the latter are technologically similar to Xidatan 2, but also that they are demonstrably connected to Xidatan 2 through utilization of the same stone raw materials, which includes a chemically distinctive obsidian. Contrary to most accounts of Tibetan Plateau colonization, our results suggest that the earliest substantial occupations on the interior Tibetan Plateau above 4000 m asl may date to the Pleistocene/Holocene transition.